Metal and metal oxide nanomaterials for heavy metal remediation: novel approaches for selective, regenerative, and scalable water treatment - Olawade, David B.; Wada, Ojima Z.; Egbewole, Bamise I.; Fapohunda, Oluwaseun; Ige, Abimbola O.; Usman, Sunday Oluwadamilola; Ajisafe, Olawale (Frontiers in Nanotechnology, 2024)
Heavy metal contamination in water sources poses a significant threat to environmental and public health, necessitating effective remediation strategies. Nanomaterial-based approaches have emerged as promising solutions for heavy metal removal, offering enhanced selectivity, efficiency, and sustainability compared to traditional methods. This comprehensive review explores novel nanomaterial-based approaches for heavy metal remediation, focusing on factors such as selectivity, regeneration, scalability, and practical considerations. A systematic literature search was conducted using multiple academic databases, including PubMed, Web of Science, and Scopus, to identify relevant articles published between 2013 and 2024. The review identifies several promising nanomaterials, such as graphene oxide, carbon nanotubes, and metal-organic frameworks, which exhibit high surface areas, tunable surface chemistries, and excellent adsorption capacities. Surface functionalization with specific functional groups (e.g., carboxyl, amino, thiol) significantly enhances the selectivity for target heavy metal ions. Advances in regeneration strategies, including chemical desorption, electrochemical regeneration, and photocatalytic regeneration, have improved the reusability and costeffectiveness of these materials. Scalability remains a critical challenge, but recent developments in synthesis methods, such as green synthesis and continuous-flow synthesis, offer promising solutions for large-scale production. The stability and longevity of nanomaterials have been improved through surface modification and the development of hybrid nanocomposites. Integrating nanomaterials with existing water treatment infrastructure and combining them with other remediation techniques, such as membrane filtration and electrochemical methods, can enhance overall treatment efficiency and feasibility. In conclusion, nanomaterial-based approaches hold immense promise for revolutionizing heavy metal remediation and advancing sustainable water management practices. As future research is geared towards retrofitting existing treatment plants, it is equally critical to mitigate unintended environmental and public health consequences associated with the widespread production and use of nanomaterials, such as their leachability into water systems and environmental persistence.